2008
DOI: 10.1029/2007jd008434
|View full text |Cite
|
Sign up to set email alerts
|

Solar radiation budget and radiative forcing due to aerosols and clouds

Abstract: [1] This study integrates global data sets for aerosols, cloud physical properties, and shortwave radiation fluxes with a Monte Carlo Aerosol-Cloud-Radiation (MACR) model to estimate both the surface and the top-of-atmosphere (TOA) solar radiation budget as well as atmospheric column solar absorption. The study also quantifies the radiative forcing of aerosols and that of clouds. The observational input to MACR includes data from the Multiangle Imaging Spectroradiometer (MISR) for aerosol optical depths, singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(155 citation statements)
references
References 123 publications
(196 reference statements)
6
149
0
Order By: Relevance
“…Many successful applications of these data to global-and regional-scale questions are already presented in the literature. They range from assessing zonal mean or global aerosol short-wave forcing [37][38][39][40][41][42] and regional long-wave forcing [43], to improving aerosol forecasting through data assimilation [44,45], monitoring dust and pollution plume evolution [46,47] and air quality [48,49], mapping aerosol air mass type evolution [50], and validating aerosol transport model AOD simulations [51,52]. In each case, ways of exploiting the strengths of the MISR and MODIS data have been found, and in many cases, independent validation was performed specific to the application.…”
Section: Application Of Misr and Modis Aerosol Productsmentioning
confidence: 99%
“…Many successful applications of these data to global-and regional-scale questions are already presented in the literature. They range from assessing zonal mean or global aerosol short-wave forcing [37][38][39][40][41][42] and regional long-wave forcing [43], to improving aerosol forecasting through data assimilation [44,45], monitoring dust and pollution plume evolution [46,47] and air quality [48,49], mapping aerosol air mass type evolution [50], and validating aerosol transport model AOD simulations [51,52]. In each case, ways of exploiting the strengths of the MISR and MODIS data have been found, and in many cases, independent validation was performed specific to the application.…”
Section: Application Of Misr and Modis Aerosol Productsmentioning
confidence: 99%
“…The water vapor importantly decreases the incident solar radiation at the surface due to its absorption of solar radiation [12]. Figure 6a,c exhibit the vertical relative humidity (RH) in all-sky and clear conditions, which consistently and gradually decreased with a maximum decrement of approximately 10% during the monsoon season in South Asia from 2006 to 2015.…”
Section: Effects Of Water Vapormentioning
confidence: 99%
“…Both at the surface and TOA the imbalance is the same and, as noted above, is estimated to be 0.9 W m -2 . Updates in Trenberth et al (2009) included revised absorption in the atmosphere by water vapor and aerosols, since Kim and Ramanathan (2008) found that updated spectroscopic parameters and continuum absorption for water vapor increased the absorption by 4-6 W m -2…”
Section: The Global Energy Budgetmentioning
confidence: 99%